Front Cover: Area Oversizing of Lithium Metal Electrodes in Solid‐State Batteries: Relevance for Overvoltage and thus Performance? (ChemSusChem 10/2021). Issue 10 (28th April 2021) - Stolz, Lukas; Homann, Gerrit; Winter, Martin; Kasnatscheew, Johannes
Abstract : The Front Cover shows batteries (shaped as rockets) with differences in cell design, that is, with varied area of Li anode relative to the area of the cathode (NMC) and the solid polymer electrolyte (SPE). These apparently inconspicuous area variations should not be disregarded, in particular at lower temperature (and/or higher rates), as they can boost the power‐ and energy density and lead to significant performance differences. Consequently, for a systematic R&D and comparability of interlaboratory systems and data, area oversizing should be also specified in protocols and reports alongside with other relevant factors for cell performance. More information can be found in the Full Paper by L. Stolz et al .